السياسة الخارجية الأمريكية تجاه منطقة المغرب العربي (2009-2017 - مراح, سفيان (جامعة الوادي University of Eloued, 2017)
عرفت الساحة الدولية بعد نهاية الحرب الباردة مجموعة من التحولات، سواء على مستوى الفاعلين الدوليين، حيث ظهر العديد من الفواعل غير الدولة ساعدتهم ثورة المعلومات والاتصالات التي ميزت هذه المرحلة على التأثير في صياغة التفاعلات الدولية. إن السیاسة الخارجیة لأي دولة هي وسیلة تعمل من خلالها الدول إلى إبراز تأثیرها الإقليمي والدولي في منطقة معینة ، كما أنها تحاول بسط سيطرتها ونفوذها من خلال تقوية سیاستها الخارجیة ، كما أنها تعتمد على طرق ووسائل وآليات تقوم باتخاذها للتأثیر على الدول المحیطة بها . إن السیاسة الخارجیة الأمريكية تجاه المغرب العربي هي عبارة عن توجهات وامتداد للسياسات المتزامنة للولايات المتحدة تجاه المنطقة ، ولكن سیاسة أمريكا كانت أكثر تأثرا وأكثر اهتماما بالمنطقة لأنها جاءت بعد أحداث وقعت داخل الولایات المتحدة الأمریكیة ، من شأنها أن تهدد الأمن القومي لأمريكا. كما أن الاكتشافات النفطية الأخیرة في المنطقة أسهمت في تزايد هذا الاهتمام والذي أدى الى اعتماد سیاسات وآليات مختلفة من أجل الوصول الى هذه الموارد التي تحاج إلیها الولایات المتحدة الأمریكیة من أجل تقوية اقتصادها وهيمنتها على دول العالم بشكل عام المغرب العربي الضعیفة على وجه الخصوص After the end of the Cold War, the international scene was characterized by a series of transformations, both at the level of international actors, where many non-state actors emerged, helped by the information and communication revolution that characterized this phase in influencing the formulation of international interactions. The foreign policy of any country is a means by which countries can highlight their regional and international influence in a particular region. They also try to extend their control and influence by strengthening their external policies. They also depend on the ways, means and mechanisms they use to influence the countries surrounding them. The US foreign policy toward the Maghreb is a trend and extension of US policy toward the region, but America's policy has been more affected and more interested in the region because it came after events in the United States that would threaten America's national security. The recent oil discoveries in the region have contributed to this growing interest, which has led to the adoption of different policies and mechanisms in order to reach these resources that the United States needs in order to strengthen its economy and its domination over the countries of the world in general and the weak Maghreb in particular
نظم سياسية مقارنة وحكم راشد
Keywords: السياسة الخارجية الأمريكية، المغرب العربي، التنمية الاقتصادية، مبادرة بان ساحل، مبادرة ايزنستات.; US foreign policy, Arab Maghreb, economic development, Pan-Sahel initiative, Eisenstadt initiative